Analisis Faktor–Faktor Risiko Kejadian Filariasis - Reyke Uloli, Soeyoko, Sumarni (Fakultas Kedokteran Universitas Gadjah Mada, 2008)
Background: According to WHO report 2001 filariasis, commonly known as elephantiasis is one of communicable disease which still becomes a public health problem in Indonesia, particularly in rural areas. Filariasis disease can cause permanent deformity, i.e. swollen legs, arms and genital regardless of sexes. Further impact of such a condition is that the sufferers cannot work normally and depend their lives to others. Filariasis disease brings great social, cultural, economic and psychological impact. Out of five districts in the province of Gorontalo, District of Bonebolango shows the highest endemic. The report shows that out of 326 people whose blood has been examined, 105 turn out to be positive (mf rate=34.4%). They are concentrated at one sub district, i.e. sub district of Boneraya (survey 2002), exceeding endemic borderline of an area with mf rate <1% which becomes a threat to economic stability of the area. WHO declares the Global Goal of Elimination of Lympathic Filariasis as a Public Health Problem by 2020, and Indonesia makes a follow up by determining filariasis elimination as a priority program of communicable disease eradication. Environmental, behavioral and social cultural factors are risk factors which minimize prevalence of filariasis.Objective: To identify risk factors related to cases of filarisis at District of Bonebolango, Province of Gorontalo.Method: The study was observational with case control design. Odds Ratio (OR) was used to find out risk factor estimation of filariasis prevalence. Interview was conducted to respondents with positive microfilaria and equal control. Total samples were as many as 140 respondents. Data analysis used Chi Square and logistic regression.Result: The result of univariable and bivariable analysis showed that risk factors related to filariasis prevalence were behavioral factors, i.e. use of mosquito net (OR=11, 5), use of ventilation wire screen (OR=2.078), use of long sleeves (OR=0, 014), knowledge (OR=2, 004) and environmental (OR=2, 215) However, the result of multivariable analysis showed that the risk factors were behavioral with such as use of mosquito net (OR=9, 568), use of long sleeves (OR=2, 870), knowledge (OR=2, 485) and environmental (OR=3.563)Conclusion: Behavioral (do not used of mosquito net and do not used long sleeves), Social cultural (low knowledge) and environmental factors were risk factors of filariasis.Keywords: behavioral, social cultural, environmental, risk of filariasis, case control